Comparative study of commercial available mono-crystalline and poly-crystalline silicon solar panel - Nayeem, Farzana; Natasha, Adnin Tazrin; Nawar, Saraf (BARC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.